Peranan Guru PPKN dalam Menumbuhkan Sikap Nasionalisme dan Pembentukan Karakter Peserta Didik di SMK Ganesa Satria 2 Depok - Iis Dewi Lestari (Sosio e-Kons, 2020)
Nasionalism is a transcendent value of Pancasila and students must have fill independence as a next generation to give the contributions  for our country. So it can come true of students character can competitives and tough in the middle of globalization. The purpose of this study is to find the PPKN teacher for developing the nasionalism character of students in SMK Ganesa Satria 2 Depok. Methodology research is descriptive. Technique data collection was carried out by interviews, observations and documentation. Technique data analysis in this research using reduction data, presentation of data, and withdrawal of conclusion. The results of this research are 1) PPKn teacher in SMK Ganesa Satria 2 Depok have very large role in developing an attitude of nationalism and the formation of the students character are implement through subjects PPKn, 2)through PPKn training teacher, the organization of  OSIS in this school can growing the nationalism attitude and form students character appropiate transcendet value of Pancasila, 3)Growing attitude of nationalism student character not only job for the PPKn teacher but its job for the other teacher in the school and specially for their parents, 4) PPKn teacher have high quality to growing the nasionalism students character  at SMK Ganesa Satria 2 Depok, its can show from his job performance as a teacher have good quality and his profesionalism as a teacher did obligations and excercise right will be models for the students in formation of students character.